Evaluating the Performance of Fertilizer Draw Solutions by Using the Modified Cellulosic Composite Forward Osmosis Membranes - Ahmed, Doaa F.; Isawi, Heba; Elbayaa, A.A.; Badway, Nagwa A.; Shawky, Hosam (Journal of Membrane and Separation Technology, 2022)
This paper deals with various fertilizer influences to draw solutions to the neat CTA/CA, MA/CTA/CA, and the Al2O3/MA/CTA/CA nanocomposite (NC) modified membrane. Also, the applicability of the neat CTA/CA, MA/CTA/CA, and The Al2O3/MA/CTA/CA nanocomposite (NC) modified membrane display high water flux when it used to desalinate brine water sample collected from the brine mid-stream from Mersa Matruh area, North-Western Coast of Egypt. The salinity of the collected sample is 12760 mg/L and PH (8.5) and used as FS, and 1M from different fertilizer draw solutes (DFDS) include KCl, NH4Cl, (NH4)2SO4, and K2HPO4 used as DS. The results reveal that the flux was KCl and NH4Cl (17.8 L/m2.h) and followed by (NH4)2SO4 (17.1 L/m2.h) and K2HPO4 (16.6 L/m2.h) using the natural saline water as FS using Al2O3/MA/CTA/CA NC modified membrane. The reusability test of the synthesised Al2O3/MA/CTA/CA NC modified membrane showed good sustainability during the 1260 min continuous test. The FO application displayed a great potential to be interested in brine wastewater desalination and enhanced water source sustainability to use in agriculture fertigation.